2014
DOI: 10.3389/fmicb.2014.00332
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell genomics reveals features of a Colwellia species that was dominant during the Deepwater Horizon oil spill

Abstract: During the Deepwater Horizon (DWH) oil spill in the Gulf of Mexico a deep-sea hydrocarbon plume developed resulting in a rapid succession of bacteria. Colwellia eventually supplanted Oceanospirillales, which dominated the plume early in the spill. These successional changes may have resulted, in part, from the changing composition and abundance of hydrocarbons over time. Colwellia abundance peaked when gaseous and simple aromatic hydrocarbons increased, yet the metabolic pathway used by Colwellia in hydrocarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 37 publications
(95 reference statements)
9
101
1
Order By: Relevance
“…The bar represents 10% estimated sequence divergence. oxidize methane (Lai et al, 2012;Mason et al, 2014). However, the positive correlation of these oligotypes with methane oxidation rates implies either their indirect involvement in this process (for example, through oxidation of co-metabolites or reaction byproducts) or their coexistence with methane oxidizers (for example, in plume samples, where methane, alkanes and PAHs coexisted) or possibly an unrecognized potential to oxidize methane.…”
Section: Environmental Factors Driving Oligotype Distribution and Abumentioning
confidence: 99%
“…The bar represents 10% estimated sequence divergence. oxidize methane (Lai et al, 2012;Mason et al, 2014). However, the positive correlation of these oligotypes with methane oxidation rates implies either their indirect involvement in this process (for example, through oxidation of co-metabolites or reaction byproducts) or their coexistence with methane oxidizers (for example, in plume samples, where methane, alkanes and PAHs coexisted) or possibly an unrecognized potential to oxidize methane.…”
Section: Environmental Factors Driving Oligotype Distribution and Abumentioning
confidence: 99%
“…4). This pathway was the same as estimated in P. butanovora [17] and in a Colwellia species [29]. It was clear that the butane oxidization was inhibited by butanol accumulation, known as intermediate metabolite feedback inhibition that is a common mechanism for organisms to control the biosynthetic pathways [30][31][32].…”
Section: Discussionmentioning
confidence: 94%
“…Members of Colwelliaceae are also known to degrade organic matter, such as aromatic hydrocarbons, which are stable in aquatic environments (Mason et al, 2014). Moreover, the bacterial species belonging to the families Rhodobacteraceae (Wagner-Döbler and Biebl, 2006) and Colwelliaceae (Mason et al, 2014) have been reported to consume nitrate via denitrification pathways.…”
Section: Bacterial Community Dynamicsmentioning
confidence: 99%
“…Members of Colwelliaceae are also known to degrade organic matter, such as aromatic hydrocarbons, which are stable in aquatic environments (Mason et al, 2014). Moreover, the bacterial species belonging to the families Rhodobacteraceae (Wagner-Döbler and Biebl, 2006) and Colwelliaceae (Mason et al, 2014) have been reported to consume nitrate via denitrification pathways. Therefore, in the snow solution-treated seawater, increased nitrate and organic matter leading to more yellow particles and microalgal cells, would induce the growth of heterotrophic bacteria (including representatives from the Colwelliaceae and Rhodobacteraceae), implying consequences for the carbon cycle in these aerosol-affected waters.…”
Section: Bacterial Community Dynamicsmentioning
confidence: 99%